In-depth Temporal Transcriptome Profiling of Monkeypox and Host Cells using Nanopore Sequencing - Kakuk, Balázs; Dörmő, Ákos; Csabai, Zsolt; Kemenesi, Gábor; Holoubek, Jiří; Růžek, Daniel; Prazsák, István; Dani, Virág Éva; Dénes, Béla; Torma, Gábor; Jakab, Ferenc; Tóth, Gábor E; et al. (Scientific data, 2023)
The recent human Monkeypox outbreak underlined the importance of studying basic biology of orthopoxviruses. However, the transcriptome of its causative agent has not been investigated before neither with short-, nor with long-read sequencing approaches. This Oxford Nanopore long-read RNA-Sequencing dataset fills this gap. It will enable the in-depth characterization of the transcriptomic architecture of the monkeypox virus, and may even make possible to annotate novel host transcripts. Moreover, our direct cDNA and native RNA sequencing reads will allow the estimation of gene expression changes of both the virus and the host cells during the infection. Overall, our study will lead to a deeper understanding of the alterations caused by the viral infection on a transcriptome level.
Keywords: nanopórové sekvenování; stanovení celkové genové exprese; Nanopore Sequencing; opičí neštovice; Gene Expression Profiling; komplementární DNA; Humans; DNA, Complementary; Mpox, Monkeypox; Transcriptome; lidé; transkriptom